Network Survival Strategies of Migrant Entrepreneurs in Large Cities: Analysis of Albanian Firms in Milan. Issue 9 (19th October 2020) - Tubadji, Annie; Fetahu, Elvira; Nijkamp, Peter; Hinks, Timothy
ABSTRACT: This paper addresses the role of cultural bias (preference for what is culturally more akin) in the entrepreneurial choice regarding different types of social networks in the context of urban mixed embeddedness. We test empirically the presence and aftermaths of this cultural bias, drawing on evidence from a natural experiment with regard to Albanian ethnic entrepreneurs in the city of Milan, Italy. Namely, these entrepreneurs are exposed to the same mixed urban embeddedness and, when we control for firm characteristics, the only discriminating component explaining their success is their choice of social network. We focus on the choice over three types of social networks, classified according to varying degrees of cultural distance between the network and the entrepreneur: (a) the indigenous population, (b) the local Albanian diaspora, and (c) fellow citizens residing in the country of origin, Albania (i.e., transnational networking). We employ a novel method for reverse engineering of preferences for networking by using a Kaplan-Meier estimator and a propensity-score matching technique. We find that strategic network liaisons with locals is actually the most beneficial social network for ethnic firm performance. However, it is social networking within the culturally closer local Albanian diaspora that is the most common behaviour.